Linear polarization on radar cross section measurement for tank miniature - Muhammad Panji Praja; Wahyu Pamungkas (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2022)
The use of radar technology, especially for the interests of state defense and security, has become the focus of development launched by the government of Indonesia. Equipment and vehicles in the defense and security sector are the top priority to be detected using radar technology. When a radar transmitter transmits its signal towards a target, some part of the signal will bounce in all directions or scattering, including to the receiver and some will be absorbed by the radar target. The radar target is assumed to have a small size, with the aim of focusing more on the beamwidth of the radar transmitting antenna to the target. This research has a focus on measuring radar targets in the form of defense equipment in the form of tanks made in miniature which are smaller than their original forms. The selected antenna polarization uses linear polarization with vertical and horizontal types. Each polarization will be compared with the value of the radar cross section (RCS) in the combination of the same polarization and different polarization. The measurement results show that the largest RCS value is obtained at an angle of 200° by 13 with a combination of Horizontal-Horizontal polarization and the smallest RCS value is obtained at an angle of 50° by -4 with a combination of Horizontal-Vertical polarization. With the results of these measurements, it can be concluded that the measurement of RCS for defense and security equipment can be carried out by measuring the miniature of the defense and security equipment